Audit of the two-week pathway for patients with suspected cancer of the head and neck and the influence of socioeconomic status. Issue 5 (June 2019) - Rogers, S.N.; Staunton, A.; Girach, R.; Langton, S.; Lowe, D.
Abstract: Rates of head and neck cancer are high in patients with a low socioeconomic status (SES) and outcomes are often poor. The degree to which people from different socioeconomic groups use the fast-track, two-week suspected cancer referral system is, however, unclear. The aim of this audit was therefore to analyse these referrals with reference to SES, and to focus on differences in clinical characteristics, source of referral, and rates of disease. The sample included all patients who were referred to the head and neck department at an inner-city hospital in the northwest of England between July and September 2017. According to the Index of Multiple Deprivation (IMD), most (62%) of them lived in the most deprived quintile. A total of 390 referrals were analysed of which 60% were female, 53% were under 60 years of age, 33% smoked, and 69% consumed fewer than 10 units of alcohol/week. Only 24 were referred by dentists, but these accounted for almost one quarter of those referred to maxillofacial surgery. Common symptoms included a swelling or lump (n = 153, 39%), hoarseness (n = 101, 26%), ulcer (n = 29, 7%), and sore throat (n = 23, 6%). Forty-five per cent were referred with other symptoms. A total of 28 (7%) were diagnosed with cancer of the head and neck. Rates were higher in patients referred by dentists (p = 0.02) and in those who drank more alcohol (p = 0.02). The positive predictive value was higher in the least deprived (17%) than in the most deprived (6%). In primary care, more education that is aimed specifically at people of lower SES might reduce the number of "worried well" and lessen the pressure on departments to achieve the two-week target.